Malaysian initiatives to support sustainable and responsible investment (SRI) especially through Sukuk approach / Muhammad Zarunnaim Wahab and Asmadi Mohamed Naim - Wahab, Muhammad Zarunnaim; Mohamed Naim, Asmadi (Universiti Teknologi Mara Selangor, 2019)
This paper attempts to discuss the initiatives offered by the Malaysian’s government to support the SRI primarily through Sukuk approach. This paper is conceptual; thus, the methodology of this paper is qualitative focusing on document analysis method by analysing previous researches, books, reports, official website and articles. Based on the analysis, this paper found four main initiatives offered by Malaysia's government to support SRI approaches, and those are guidelines and frameworks, tax deductions, tax initiatives and Green Technology Financing Scheme. This paper useful to strengthen current studies related to SRI, especially in Malaysian contexts. Besides, this paper also provides a clear picture related to initiatives taken by Malaysia to support SRI and thus, might offer a new dimension in SRI implementation.